The Correlation of Muscle Mass and Fat with Leg Power of 16 Senior Highschool Basketball Athlete - Helmi, Mohamad Farhan; Setiakarnawijaya, Yasep; Kuswahyudi, Kuswahyudi (Universitas Negeri Semarang, 2023)
This study aims to explore the relationship between muscle mass and fat with lower limb power in high school basketball athletes from SMA N 16 Jakarta. The survey method was employed, involving measurement and data analysis using a quantitative correlational approach. The results of the study indicate a significant relationship between muscle mass and fat with lower limb power in athletes. These findings contribute significantly to understanding how body composition, particularly muscle mass and fat, can influence overall body strength, especially in the lower limbs. The conclusion of this research confirms the existence of a relationship between muscle mass, fat, and lower limb power in high school basketball athletes. Thus, the research objective to evaluate this relationship is achieved. Practical implications of this study include an enhanced understanding of athlete body quality. However, it is important to note that factors beyond muscle mass and fat, such as environmental conditions, physical health, and psychological aspects, can also impact muscle strength.